Are Shocks to Energy Consumption per capita in Turkey Permanent or Temporary? - (:unkn) unknown (IGI GLOBAL, 2017)
Turkey achieved an average growth rate of five percent during 2003-2013. In the same period, annual average growth rate was four percent in primary energy consumption. This indicates the significance of energy consumption for economic growth. In this context, the energy sector is one of the most important areas in Turkey's national strategy documents. Geostrategic position of Turkey in terms of energy resources affects Turkey's energy policies and strategies. In this framework, the main purpose of the study is to analyze empirically the effects of shocks in the energy sector. In this context, the permanent or temporary effects of shocks on energy use were investigated for the period 1960-2012. According to the test results, shocks had permanent effects on the energy consumption in Turkey. Permanent effects of shocks on the energy use indicate the importance of strategic energy policies for Turkey.
Keywords: UNIT-ROOT